IVF policy and global/local politics: The making of multiple-embryo transfer regulation in Taiwan - Wu, Chia-Ling (Social science & medicine (1982), 2012)
This paper analyzes the regulatory trajectory of multiple-embryo transfer in in-vitro fertilization (IVF) in Taiwan. Taking a latecomer to policy-making as the case, it argues the importance of conceptualizing the global/local dynamics in policy-making for assisted reproductive technology (ART). The conceptual framework is built upon recent literature on standardization, science policy, and global assemblage. I propose three interrelated features that reveal the “global in the local”: (1) the power relationships among stakeholders, (2) the selected global form that involved actors drew upon, and (3) the re-contextualized assemblage made of local networks. Data included archives, interviews, and participant observation. In different historical periods the specific stakeholders selected different preferred global forms for Taiwan, such as Britain’s code of ethics in the 1990s, the American guideline in the early 2000s, and the European trend in the mid-2000s. The global is heterogeneous. The failure to transfer the British regulation, the revision of the American guideline by adding one more embryo than it specified, and the gap between the cited European trend and the “no more than four” in Taiwan’s 2007 Human Reproduction Law all show that the local network further transforms the selected global form, confining it to rhetoric only or tailoring it to local needs. Overall, Taiwanese practitioners successfully maintained their medical autonomy to build a ‘flexible standardization’. Multiple pregnancy remains the most common health risk of IVF in Taiwan. ► The role of the “global/transnational” in ART policy-making has been under-researched. ► Examining latecomers’ regulatory formation can illuminate the specificity of global/local dynamics. ► In creating an IVF standard in Taiwan, stakeholders selected diverse global forms as a reference. ► The configuration of the selected global forms depended on the encountering local network to make a policy assemblage. ► IVF doctors in Taiwan managed to build a flexible standardization in multiple-embryo transfer regulation.